Production of knowledge in school gymnastics: the reflexive pedagogical practice in action - Telma Adriana Pacifico Martineli (Journal of Physical Education (Maringá), 2008)
This article aims at contributing to reflections on Physical Education, presenting a reflexive pedagogical experience. The investigation-in-action (ELLIOTT, 1994) mediated by the reflexive practice (SCHÖN, 2000) through observation, pedagogical intervention and interviews has been adopted as the theorical-metodological referential. Two classes samples were taken whose target was to produce school knowledge. Concerning the reflexive process it was clearly evident that the students had taken their first steps in the sense of building their knowledge on physical education by working out daily concepts and moving towards the scientific conception (VYGOTSKI, 1998). Despite the institution’s complexity, conflicts and contradictions, the results showed that it is possible to produce knowledge on physical education/gymnastics by developing the reflexive pedagogical practice, facing the reality and establishing ruptures. The investigation-in-action mediated by the reflections allowed precious moments to analyze the school reality, as well as to search for means in order to intervene in this reality, and reconsider the initial formation of physical education teachers.